Effects of traditional Chinese mind–body exercises on older adults with cognitive impairment: A systematic review and meta-analysis - Yao, Ke-ru; Luo, Qin; Tang, Xi; Wang, Zhi-han; Li, Lu; Zhao, Lu; Zhou, Li; Li, Ling; Huang, Li; Yin, Xin-hong (Frontiers in Neurology, 2023)
Objective To determine the effectiveness of traditional Chinese mind–body exercises in improving cognition, memory, and executive function in older adults with cognitive impairment. Data sources Relevant English and Chinese language studies published until September 14th, 2022 were retrieved from PubMed, Web of Science, Cochrane Library, Embase, CINAHL, WAN FANG DATA, VIP Information, CNKI, and SinoMed databases. Review methods Randomized controlled trials assessing traditional Chinese mind–body exercises (Tai Chi, Baduanjin, Qigong, Mind–Body Therapies, and Yijinjing) in older adults with cognitive impairment were included. Two researchers independently identified eligible studies and extracted data. A risk-of-bias assessment was performed using the Cochrane Risk of Bias Tool. Results This study included 15 randomized controlled trials (1,127 participants) from China, Thailand and American. Most studies had a high risk of bias in the blinding of participants and researchers, one study had a high risk of bias in the random sequence generation and two studies had a high risk of bias in the incomplete outcome data. Compared with conventional therapy alone, traditional Chinese mind–body exercises significantly improved global cognitive function (p < 0.00001), and Baduanjin could improve the global cognitive function (p < 0.00001), memory function (p < 0.0001), and executive function (p < 0.0001) outcomes after treatment, and significantly improved some dimensional scores on the auditory verbal learning test after treatment (p = 0.04). Conclusion Compared with conventional therapy, traditional Chinese mind–body exercises (Tai Chi, Baduanjin, and Qigong) significantly improved global cognitive function, and Baduanjin could improve global cognitive function, memory function, and executive function in older adults with cognitive impairment. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#searchadvanced, CRD42022327563.